Repeatability of carbon dioxide and methane emissions and oxygen consumption by forage-consuming beef heifers - M.D. MacNeil; R.C. Waterman (Animal)
Gas exchange by ruminant livestock is deemed as a contributor to climate change. As such, research to reduce the production of greenhouse gasses is an emerging need. It is important that these studies reach definitive outcomes. Because the majority of cows are sustained by grazing forages, the objective of this study was to assess the variation in methane (CH4) and carbon dioxide (CO2) emissions and oxygen (O2) consumption among forage-consuming beef cattle. Recommendations as to the number of days over which data need to be collected and the numbers of experimental units that need to be used in comparing treatments can be inferred from this information. Heifers (n = 30) from a three-breed composite population of beef cattle were used in this research. They were introduced to a portable automated head-chamber system in January 2023 and had continuous access to the system through February 2024 (414 d). Data were uploaded to a server, and proprietary algorithms were used to calculate CH4 and CO2 emission and O2 consumption of the heifers. Repeatability of the daily average values was calculated, and those estimates were used to infer the accuracy of measurements obtained over varying numbers of days. The numbers of heifers that are required to achieve a specified power-of-the-test for an experiment comparing two treatments and for the comparison of an observed mean against a threshold were calculated. Methane required 45 days of measurements to obtain a mean with 80% accuracy. Carbon dioxide required data from only 28 days. Given the cost of the technology to measure gasses in the grazing situation and the recommended number of animals to utilize it at one time, some care will be required in designing appropriate experiments and to properly interpret the observed effects particularly when they are not statistically significant.